Differences between the genders in ICT skills for Finnish upper comprehensive school students: Does gender matter? - Kaarakainen Meri-Tuulia; Kivinen Antero; Kaarakainen Suvi-Sadetta (Seminar.net International Journal of Media, Technology & Lifelong Learning, 2022)
This study examined the ICT skills of Finnish upper comprehensive school students. The data has been collected from 65 municipalities around Finland for 5455 ninth graders (mean age 15.24). ICT skills were measured using a digital, performance-based ICT skill test. The test was based on the revised Finnish national core curriculum for basic education. Based on the results, there was a small, but statistically, significant difference between the genders in the total scores on the ICT skill test. More consequential differences between the genders were found in the item level analysis. As explicit item level analysis indicated, boys tended to get better scores from more technical-oriented items, while girls got better scores from school work-oriented and social interactionrelated items. The results emphasize that gender differences in ICT skills are more item specific than general. More importantly, the variation between individuals in ICT skill items was extensive and in all likelihood more influential than the gender difference as such.